The Cultural Practice of Rimpu Among Millennial Fashion Models in Rasa Bou Village, Dompu Regency: A Representation of Islamic Values - Nuraeni, Nuraeni; Nuruddin, Nuruddin; Jayadi, Suparman (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study explores the significance of Rimpu, a traditional practice in Rasa Bou Dompu Village, as a representation of Islamic values among millennial fashion models. The objective is to investigate Rimpu's cultural and religious elements and its connection to the local modelling industry. The study used a qualitative research approach and gathered data through in-depth interviews with millennial generation fashion models who regularly practice Rimpu. The results reveal that Rimpu is a symbol of modesty, purity, and spirituality, which aligns with Islamic teachings. The practice also plays a vital role in the fashion industry by showcasing the blend of local culture and modern fashion trends. This study provides valuable insights into the significance of Rimpu in contemporary Islamic fashion and highlights the need to promote and preserve traditional practices as a representation of cultural and religious values.